Characterizing the influence of racism-related stress and pandemic-related changes in social connections on cardiovascular health: Study protocol and theoretical framework - Jewel Scott; Victoria Money; Charles Ellis; Chanita Hughes-Halbert; Michelle A. Birkett; Gayenell Magwood (PLoS ONE, 2025)
Background Cardiovascular-related morbidity and mortality among young adults are rising, and disparities between young Black and White women are immense. Health behaviors including physical activity and diet are essential for optimal cardiovascular health. Psychosocial factors, such as racism, perceived stress, and lack of social support, contribute to racial inequities in cardiovascular disease, which were further exacerbated by the COVID-19 pandemic. The proposed study aims to assess the influence of racism-related stress and other social determinants of health, including social connectedness, on quality of life and cardiovascular-related health behaviors. Methods This is a concurrent, triangulation, mixed-methods study combining survey data on health behaviors, psychosocial stressors, and social networks with a thematic analysis of focus group data. Participants will be people who self-identify as Black or African American woman, between the ages of 18 and 39, residing in the southeastern United States with at least one cardiovascular disease risk factor. The primary outcome is physical activity and quality of life. Discussion The results will be informative for developing an action plan for improving cardiovascular health at a network and community-level to mitigate the predicted post-pandemic increase in cardiovascular disease. This study will provide an integrated perspective of the influence of the COVID-19 pandemic on quality of life and social relationships with implications for cardiovascular health equity.